2015
DOI: 10.1128/aem.02575-15
|View full text |Cite
|
Sign up to set email alerts
|

Premethylation of Foreign DNA Improves Integrative Transformation Efficiency in Synechocystis sp. Strain PCC 6803

Abstract: cRestriction digestion of foreign DNA is one of the key biological barriers against genetic transformation in microorganisms. To establish a high-efficiency transformation protocol in the model cyanobacterium, Synechocystis sp. strain PCC 6803 (Synechocystis 6803), we investigated the effects of premethylation of foreign DNA on the integrative transformation of this strain. In this study, two type II methyltransferase-encoding genes, i.e., sll0729 (gene M) and slr0214 (gene C), were cloned from the chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…For the methylation of the HIP1-related motif via M.Ssp6803I, a role in DNA repair processes was previously suggested [5]. With regard to transformation, it was reported that the methylation of plasmid DNA in E. coli expressing M.Ssp6803I encoded by the Synechocystis 6803 gene slr0214 prior to transformation led to an 11- to 161-fold-higher efficiency in the subsequent integrative transformation of Synechocystis 6803 [39]. In contrast, expression of M.Ssp6803II from gene sll0729 methylating GGCC [7] had no measurable impact on transformation efficiencies [39].…”
Section: Discussionmentioning
confidence: 99%
“…For the methylation of the HIP1-related motif via M.Ssp6803I, a role in DNA repair processes was previously suggested [5]. With regard to transformation, it was reported that the methylation of plasmid DNA in E. coli expressing M.Ssp6803I encoded by the Synechocystis 6803 gene slr0214 prior to transformation led to an 11- to 161-fold-higher efficiency in the subsequent integrative transformation of Synechocystis 6803 [39]. In contrast, expression of M.Ssp6803II from gene sll0729 methylating GGCC [7] had no measurable impact on transformation efficiencies [39].…”
Section: Discussionmentioning
confidence: 99%
“…Natural transformation with plasmids was performed via an optimized protocol based on previous reports. [54][55][56][57][58][59][60] Synechocystis cells were grown to the mid-log phase with OD 730 = 0.5-1.2 in liquid BG11 medium. Then, the cell culture was collected by centrifugation at 5000 Â g for 5 min and washed twice with fresh liquid BG11 medium without antibiotics, and finally resuspended into fresh liquid BG11 medium at a density of 1 Â 10 9 cellsÁmL À1 (OD 730 = 2.5).…”
Section: Transformation Of Synechocystismentioning
confidence: 99%
“…Similarly, deletion of a type I restriction endonuclease in T. elongatus BP-1 also leads to higher transformation efficiencies [ 115 ]. Furthermore, pre-methylation of DNA for transformation could aid in overcoming transformability issues [ 116 , 117 ] ( Figure 3 C).…”
Section: Targeted Manipulation Of Natural Competencementioning
confidence: 99%